The Issue of Habit and its Applications According to the Fundamentalists - saeed, Zeyad (Islamic Sciences Journal, 2023)
Islamic Sharia is keen to take into account people’s traditions and customs that they followed and made them among the contents of Islamic Sharia provided that it does not violate Sharia. Thus it is forming a fabric of heavenly laws with traditions from the experience of societies such as rejecting unpleasant things and approving virility, so the research is keen to investigate the various aspects of the rule of habit. Court and its applications how they are dealt with for the fundamentalists.